Training load and post-exercise recovery following varied game intervals in 3x3 basketball - Paulauskas, R.; Kamarauskas, P.; Gonçalves, B.; Figueira, B. (Journal of Human Kinetics, 2025)
The study aimed (I) to quantify external and internal training loads during simulated 3x3 basketball games of 1, 2, 3, and 4 min, each followed by 1-min rest intervals; and (II) to assess the heart rate and muscle oxygen saturation recovery rates following, 1-, 2-, 3-, and 4-min periods of play. Twelve (n = 12) elite male 3x3 basketball players (age: 26.6 ± 5.6 years, body height: 196.8 ± 5.5 cm, body mass: 92.0 ± 9.5 kg, training experience: 15.4 ± 3.9 years, and 3x3 basketball training experience: 4.8 ± 1.6 years) from the Lithuanian national team participated in two controlled simulated games. Differences between playing intervals were analysed using a repeated-measures factorial analysis of variance. The results demonstrated that extended 3x3 basketball play duration led to significant increases in total distance covered, the sprint count, and the jump count, while diminishing dynamic responses in the deceleration rate, average speed, the jump rate, and high-intensity effort. Notably, SmO2 levels exhibited stability during recovery intervals regardless of activity duration, whereas heart rate recovery improved markedly, particularly following extended play periods. This knowledge is instrumental in refining training protocols for 3x3 basketball, emphasizing the necessity of recovery strategies tailored to specific play duration.